If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2m + 3) = 0 Reorder the terms: 7(3 + 2m) = 0 (3 * 7 + 2m * 7) = 0 (21 + 14m) = 0 Solving 21 + 14m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 14m = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 14m = 0 + -21 14m = 0 + -21 Combine like terms: 0 + -21 = -21 14m = -21 Divide each side by '14'. m = -1.5 Simplifying m = -1.5
| 5(3m-6)=150 | | 5(x-2)-4=-6(-3x+4)-9x | | 3m^2-19m-72=0 | | 4w+7=23 | | 10+2r=6-6(7r-8) | | -2+x/3=13 | | 7v+8=2v+3 | | 11=-v+268 | | (6-1)(2x+5)=168 | | (a-3)/5-(5(a-3))/8=(5a+25)/4 | | -(2k+8)-(3k-7)= | | (6-1)+(2x+5)=168 | | 275-y=50 | | 2c^2-5=3 | | .36X-.035Y=10 | | 6a-5+3a=4a-3 | | -4v/7=-24 | | 1/3x-1/4(x-2)=4x | | -9/5=3y | | .36X+.035Y=.10 | | 2(Z-38)=5(Z-59) | | 11/15-(-3/5) | | 3/4n=-24 | | -5/8v=10 | | x^2+9t+4=0 | | 36X/16+3.5Y/16=10 | | .6(15c+10)=12c-9 | | 25.6=y/8 | | 6/5x-1/11=-6 | | 1/7x+1/3y | | -3(x-8)-5=9*(x+2)+1 | | 7a-4+29=3a-2 |